Liraglutide ameliorates diabetic-induced testicular dysfunction in male rats: role of GLP-1/Kiss1/GnRH and TGF-β/Smad signaling pathways - Fathy, Maha Abdelhamid; Alsemeh, Amira Ebrahim; Habib, Marwa A.; Abdel-nour, Hanim M.; Hendawy, Doaa M.; Eltaweel, Asmaa Monir; Abdelkhalek, Adel; Ahmed, Mona M.; Desouky, Maha K.; Hua, Jinlian; Fericean, Liana Mihaela; Banatean-Dunea, Ioan; et al. (Frontiers in Pharmacology, 2023)
Introduction: Glucagon-like peptide -1 (GLP-1) is released by intestinal cells to stimulate glucose-dependent insulin release from the pancreas. GLP-1 has been linked to ameliorating obesity and/or diabetic complications as well as controlling reproductive function. Liraglutide is a GLP-1 receptor agonist (GLP-1RA) with 97% homology with GLP-1. The main objective of this study was to investigate the ameliorative role of liraglutide in diabetic-induced reproductive dysfunction in male rats. Methods: Rats were randomly allocated into 3 groups; a control group, a diabetic group, and a liraglutide-treated diabetic group. Results: In the diabetic group, a significant increase in BMI, FBG, HbA1c, HOMA-IR, TC, TAG, LDL, IL6, TNFα, and MDA, as well as decreased serum insulin, HDL, GSH, total testosterone, LH, and FSH, were shown compared to the control group. Furthermore, A significant downregulation in relative hypothalamic gene expression of GLP-1R, PPAR-α, PGC-1α, kiss, kiss1R, leptin, leptin R, GnRH GLP-1R, testicular PGC-1α, PPARα, kiss1, kiss1R, STAR, CYP17A1, HSD17B3, CYP19A, CYP11A1, and Smad7, as well as upregulation in hypothalamic GnIH and testicular TGF- β and Smad2 expression, were noticed compared to the control group. Liraglutide treatment significantly improved such functional and structural reproductive disturbance in diabetic rats. Conclusion: GLP-1RAs ameliorated the deleterious effects of diabetes on reproductive function by targeting GLP-1/leptin/kiss1/GnRH, steroidogenesis, and TGF- β/Smad pathways.